SAT0219 Methotrexate-Induced Reduction in Concentration of HBA1C in Rheumatoid and Psoriatic Arthritis is Not Correlated with Sustained Increase in Erythrocyte ZMP or Urinary Aicar Concentration. (9th June 2015) - Perdan-Pirkmajer, K.; Pirkmajer, S.; Thevis, M.; Thomas, A.; Praprotnik, S.; Hočevar, A.; Rotar, Ž.; Gašperšič, N.; Sodin-Šemrl, S.; Žibert, J.; Omersel, J.; Chibalin, A.; et al.
Abstract : Background: Methotrexate (MTX) may reduce the risk of developing type 2 diabetes in rheumatoid (RA) and psoriatic arthritis (PsA). Animal studies suggest that MTX could reduce this risk by inducing intracellular accumulation of 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranosyl-5'-monophosphate (ZMP). However, whether MTX therapy leads to chronic increase in ZMP concentration in RA or PsA patients has not been determined. Objectives: We explored whether improvements in glucose homeostasis during MTX therapy in RA or PsA are associated with changes in concentration of ZMP or its metabolite 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR). Methods: Newly diagnosed nondiabetic, MTX-naïve, RA (2010 ACR/EULAR criteria) and PsA (CASPAR criteria) patients were enrolled between December 2012 and June 2013. Patients were treated according to the treat to target approach. DAS28ESR and the metabolic parameters were followed at baseline and at 1, 2, 3 and 6 months after MTX initiation. Concentration of glycated hemoglobin HbA1c and HOMA-IR (fasting glucose (mmol/l) x fasting insulin (μU/ml)/22.5) were determined to assess glucose homeostasis. Erythrocyte ZMP concentration and urinary AICAR concentration were measured with liquid chromatography-mass spectrometry at baseline and at 1 and 6 months. Data were analyzed using repeated measures ANOVA or Friedman test, followed by an appropriate post hoc test. Results: 16 RA and 10 PsA patients completed the study (16 female, 10 male). Mean age was 53±12, BMI 28.5±4.6 kg/m 2 and the initial DAS28ESR 5.3±1.3. Remission or low disease activity (DAS28ESR<3.2) was achieved in 20 out of 26 patients at 6 months. HbA1c concentration was reduced from 5.80%±0.29% (39.0±3.1 mmol/mol) at baseline to 5.52%±0.31% (36.8±3.5 mmol/mol) at 6 months ( P <0.001). HOMA-IR remained unaltered. Reduction in HbA1c concentration was observed in 19 out of 26 patients. The number of patients with prediabetes (5.7%≤HbA1c concentration at 6 months were not associated with changes in ZMP or AICAR concentration. Conclusions: Here we show that MTX therapy reduces HbA1c concentration in RA or PsA patients. However, MTX does not produce a sustained increase in erythrocyte ZMP or urinary AICAR concentration, suggesting ZMP did not accumulate during MTX therapy. Collectively, our data do not support the notion that MTX improves glucose homeostasis via chronic accumulation of ZMP. Disclosure of Interest: None declared